Elastic Module Study of the Radial Section of Guadua angustifolia Kunth Variety Bicolor - J. I. Cardenas; C. Vargas-Hernández (Advances in Materials Science and Engineering)
Elastic modulus of the radial section of the Guadua angustifolia Kunth variety Bicolor was studied by technique of propagation of acoustic waves; the signal time delay in the samples was used as the control parameter. The studies were carried out in the culm cross-section in radial direction. The results indicate that the elastic modulus and the propagation velocity of the longitudinal wave in each of the cross-sections varied from 2.5×107 to 1.6×109 Pa and from 1370 to 250 m/s for the inside and outside region of the culm, respectively. This behavior is due to the inhomogeneity, the water concentration, the fiber density, and the silicon concentration. The Raman spectroscopy analysis showed bands associated with hemicellulose, cellulose (carbon-carbon bonds), hydroxides carbon, and lignin. Silicone polymer compounds were identified by gas chromatography/mass spectroscopy.